Application of Failure Mode and Effects Analysis (FMEA) to Analyze Occupational Safety Risks in General Cargo Ship Loading and Unloading Activities at Makassar Port - Sampe Lolo, Cynthia; Husain, Firman; Sade , Juswan (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2026)
Makassar Port as one of the main ports in Indonesia has an important role in the national logistics system, but the loading and unloading activities of general cargo ships have the potential for high occupational safety risks. This study aims to identify, evaluate, and prioritize risks that can occur during the loading and unloading process at Makassar Port. The analysis of occupational safety risks in the loading and unloading activities of general cargo ships uses the Failure Mode and Effect Analysis method approach by identifying the failure mode, the impact of failure, and the cause of failure that occurs at each stage of loading and unloading activities and involves the assessment of Severity, Occurrence, and Detection to determine the Risk Priority Number (RPN). Through the application of FMEA method, an in-depth identification of work stages, failure modes, effects, causes, and Risk Priority Number (RPN) values for each work activity is obtained. The results of the analysis that show the failure mode with the highest RPN value in this study are in the loading and unloading activities which then become a reference for designing mitigation steps or appropriate repair solutions by implementing a safety briefing before starting the activity, a safety area on the dock for activities, ensuring the load is in accordance with the capacity of the lifting equipment, training for heavy equipment operators, controlling or monitoring by the PnC team, communication and mutual coordination between operators and field workers. The conclusion of this study is that the approach using the FMEA method is effective in identifying and evaluating work safety risks in loading and unloading activities. With the results of risk mapping, the port can take more targeted preventive measures.